Sistem Informasi e-Verifikasi Keuangan Pada Instansi Pemerintah Daerah - Sabto Kironowati; Tazkiyah Herdi (Ikatan Ahli Informatika Indonesia (IAII), 2019)
The development of e-government has become the focus of regional government nowdays. The move is meant to push the acceleration of an efficient and transparent governance particularly in public service improvement. One of the indicators of the success of transparency in financial management of local government is